Demographic masculinisation with increasing parity and out look of sex preference in Bundelkhand region, India - Srivastava, Shilpi; Sharma, Sanjay; Kharkwal, Sushila; Singh, Meenakshi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The objective of the study was to study status of sex ratio at birth with increasing parity and to study outlook of society toward sex preference. Methods: This is a retrospective study conducted in department of Obstetrics and Gynecology in M.L.B. medical college Jhansi, India. The data collected from records of January 2014 to December 2014. Data of total number of male and female birth also collected showing sex ratio from year 2011 to 2014 and 200 antenatal women interrogated in privacy for sex preference of unborn. Results: Sex ratio at birth in year 2014 in Bundelkhand region was 835 female per 1000 male. Sex ratio is in declining trend from year 2011 to 2014. Sex ratio in primipara was 960, which decreased to 900 per thousand in second para, further decreased to 830 and 710 female per thousand male in third and fourth para respectively. Sex preference is maximum in multigravida with previous female baby. Conclusions: Overall, our results provide clear evidence that the sex ratio at birth is decreasing in Bundelkhand. In spite of all efforts and plans there is decreasing trend of sex ratio year by year. There is decreasing trend of sex ratio with increasing parity. Social outlook toward sex preference is more male sex preference is found in multigravida having previous female baby. Male sex preference also found in primigravida and multigravida having previous male baby but in relatively low percentage.